BI’AH ARABIYAH DAN PEMEROLEHAN BAHASA - Thonthowi, Thonthowi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2007)
One of the obstacles in foreign language acquisition, including the Arabic is the minimal level of acquisition the students get. This is presumably caused by the unfavorable environment for the students to be accustomed to use the language, that encourages them to be learner-independent. For this reason, the education institution needs to develop boarding school to build the Arabic environment as an active and innovative in the process of language learning. There are some favorable factors as contributing to the language learning process and there are some other unfavorable factors hampering it. However, by involving any party and optimize the school environment, the language acquisition of the students can be optimized.